Children's subjective well-being in Africa: A comparative analysis across three countries. (September 2017) - Savahl, Shazly; Tiliouine, Habib; Casas, Ferran; Adams, Sabirah; Mekonen, Yehualashet; Dejene, Negussie; Benninger, Elizabeth; Witten, Heidi
Abstract: Recent trends in child well-being research have shown a substantial advancement in studies investigating children's subjective well-being (SWB). This advancement has raised questions concerning the measurement of SWB and the extent to which various measures can be compared across countries and diverse cultures. With a dearth of empirical data on cross-cultural comparisons, the validation of existing measures and cross-cultural comparisons and adaptations, have been identified as a critical course of action. The current study contributes to this process – it aims to report on children's SWB in three African countries (Algeria, Ethiopia, and South Africa), using two multiple item measures of SWB (the context-free Students' Life Satisfaction Scale and the domain-specific Personal Well-Being Index-School Children). Within this process the study further aims to test the structural validity of these measures and to ascertain its cross-country comparability. Data from the second wave of the Children's Worlds survey were used; and includes a randomly selected sample of 3394 children between the ages of 11–12 from Algeria (Provinces of El Bayedh, Oran, and Tlemcen), Ethiopia and South Africa (Western Cape Province). Located within the goodness of fit theoretical framework, confirmatory factor analysis and Structural Equation Modelling were used to test the overall fit structure, while multi-group confirmatory factor analysis was used to test measurement invariance. The results show appropriate fit structure for the individual models, with metric and scalar factor invariance tenable across the three countries for the Students' Life Satisfaction Scale and partial scalar invariance obtained for four items on the Personal Well-Being Index-School Children. The Algerian sample scored significantly higher than Ethiopia and South Africa on both SWB measures. Appropriate fit structure was obtained for the combined model and for the structural model, indicating adequate convergent validity with the single item Overall Life Satisfaction. Metric and partial scalar invariance was tenable for the structural model, suggesting cross-country comparability for correlations, regressions and means. The overall findings suggest that the two measures are appropriate for use with children from the three countries and that meaningful comparisons can be made between the three countries. Highlights: The study tests the structural validity and comparability of two subjective well-being measures in three African countries Data from Wave 2 of the Children's Worlds study were used with a random sample of 3394 children aged 11-12 The individual models showed appropriate fit, with metric and scalar factor invariance tenable across the countries Appropriate fit structure was also found for a combined model using context-free and domain-specific measures These results suggest that the measures are appropriate for use with children across the three countries